A Magnetohydrodynamic enhanced entry system for space transportation: MEESST - Andrea Lani; Vatsalya Sharma; Vincent F. Giangaspero; Stefaan Poedts; Alan Viladegut; Olivier Chazot; Jasmine Giacomelli; Johannes Oswald; Alexander Behnke; Adam S. Pagan; Georg Herdrich; Minkwan Kim; et al. (Journal of Space Safety Engineering, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The intersection of food security and biodiversity conservation: a review - Josefine Glamann; Jan Hanspach; David J. Abson; Neil Collier; Joern Fischer (Regional Environmental Change, 2017)

A continental‐scale analysis of feral cat diet in Australia - Tim S. Doherty; Robert A. Davis; Eddie J. B. van Etten; Dave Algar; Neil Collier; Chris R. Dickman; Glenn Edwards; Pip Masters; Russell Palmer; Sue Robinson (Journal of Biogeography, 2015)
Aim Reducing the impacts of feral cats ( Felis catus ) is a priority for conservation managers across the globe, and success in achieving this aim requires a detailed understanding of the species’ ecology across a broad spectrum of climatic and environmental conditions. We reviewed the diet of the feral cat across Australia and on Australian territorial islands, seeking to identify biogeographical patterns in dietary composition and diversity, and use the results to consider how feral cats may best be managed. Location Australia and its territorial islands. Methods Using 49 published and unpublished data sets, we modelled trophic diversity and the consumption of eight food groups against latitude, longitude, mean temperature, precipitation, environmental productivity and climate‐habitat regions. Results We recorded 400 vertebrate species that feral cats feed on or kill in Australia, including 28 IUCN Red List species. We found evidence of continental‐scale prey‐switching from rabbits to small mammals, previously recorded only at the local scale. The consumption of arthropods, reptiles, rabbits, rodents and medium‐sized native mammals varied with different combinations of latitude, longitude, mean annual precipitation, temperature and environmental productivity. The frequency of rodents and dasyurids in cats’ diets increased as rabbit consumption decreased. Main conclusions The feral cat is an opportunistic, generalist carnivore that consumes a diverse suite of vertebrate prey across Australia. It uses a facultative feeding strategy, feeding mainly on rabbits when they are available, but switching to other food groups when they are not. Control programmes aimed at culling rabbits could potentially decrease the availability of a preferred food source for cats and then lead to greater predation pressure on native mammals. The interplay between cat diet and prey species diversity at a continental scale is complex, and thus cat management is likely to be necessary and most effective at the local landscape level.

Phenological decoupling of mortality from wave forcing in kelp beds - Thibaut de Bettignies; Thomas Wernberg; Paul S. Lavery; Mathew A. Vanderklift; Jim R. Gunson; Graham Symonds; Neil Collier (Ecology, 2015)
Kelps often live in a harsh hydrodynamic environment where wave‐driven dislodgement of individuals can alter the biodiversity and functioning of reef systems, and increase production in coastal ecosystems adjacent to reefs. The current paradigm is that winter storms tear kelps from reefs once hydrodynamic forces exceed attachment or tissue strength—a threshold response that implies a pulsed relationship between wave forces and dislodgement. Here, we challenge this understanding by showing how kelp phenology can decouple susceptibility to dislodgement from seasonal patterns in wave forces. We measured kelp dislodgement rates and hydrodynamic forces at nine subtidal reefs over two years ( n = 4320 kelps tagged and monitored). Contrary to expectation, we found relatively low and constant dislodgement rates for all reefs (13% ± 6% [mean per season ± SD]) in spite of a strong temporal pattern in wave action and extreme water velocities (winter peaks up to 3–4 m/s). A biomechanical model, based on the balance between kelp attachment strength and hydrodynamic drag, demonstrated that severe reduction in individual kelp size toward winter (>50% decrease in biomass for all sites) minimized drag and made the kelps less susceptible to high water velocities, allowing individuals to survive storm velocities over 3–4 m/s. We conclude that the timing of reduced susceptibility to disturbance, through the seasonal reduction of individual kelp biomass that coincides with times of highest water velocities is critical to the dynamics of kelp dislodgement and survival. We propose that phenological processes maintain many kelp beds in a higher degree of population stability and equilibrium with hydrodynamic forces than previously believed.

Management of duodenal adenomatosis in FAP: single centre experience - Musa Drini; Anthony Speer; Christopher Dow; Neil Collier; Prithi Bhathal; Finlay A. Macrae (Familial Cancer, 2012)

Contemporary habitat loss reduces genetic diversity in an ecologically specialized butterfly - Neil Collier; Mike Gardner; Mark Adams; Clive R. McMahon; Kirsten Benkendorff; Duncan A. Mackay (Journal of Biogeography, 2010)
Aim This study investigated the influence of contemporary habitat loss on the genetic diversity and structure of animal species using a common, but ecologically specialized, butterfly, Theclinesthes albocincta (Lepidoptera: Lycaenidae), as a model. Location South Australia. Methods We used amplified fragment length polymorphism (AFLP) and allozyme datasets to investigate the genetic structure and genetic diversity among populations of T. albocincta in a fragmented landscape and compared this diversity and structure with that of populations in two nearby landscapes that have more continuous distributions of butterflies and their habitat. Butterflies were sampled from 15 sites and genotyped, first using 363 informative AFLP bands and then using 17 polymorphic allozyme loci ( n = 248 and 254, respectively). We complemented these analyses with phylogeographic information based on mitochondrial DNA (mtDNA) haplotype information derived from a previous study in the same landscapes. Results Both datasets indicated a relatively high level of genetic structuring across the sampling range (AFLP, F ST = 0.34; allozyme, F ST = 0.13): structure was greatest among populations in the fragmented landscape (AFLP, F ST = 0.15; allozyme, F ST = 0.13). Populations in the fragmented landscape also had significantly lower genetic diversity than populations in the other two landscapes: there were no detectable differences in genetic diversity between the two continuous landscapes. There was also evidence ( r 2 = 0.33) of an isolation by distance effect across the sampled range of the species. Main conclusions The multiple lines of evidence, presented within a phylogeographic context, support the hypothesis that contemporary habitat fragmentation has been a major driver of genetic erosion and differentiation in this species. Theclinesthes albocincta populations in the fragmented landscape are thus likely to be at greater risk of extinction because of reduced genetic diversity, their isolation from conspecific subpopulations in other landscapes, and other extrinsic forces acting on their small population sizes. Our study provides compelling evidence that habitat loss and fragmentation have significant rapid impacts on the genetic diversity and structure of butterfly populations, especially specialist species with particular habitat preferences and poor dispersal abilities.